Effect of Aspect Ratio, Channel Orientation, Rib Pitch-to-Height Ratio, and Number of Ribbed Walls on Pressure Drop Characteristics in a Rotating Channel with Detached Ribs - K. Arun; S. V. Prabhu (International Journal of Rotating Machinery)
The present work involves experimental investigation of the effects of aspect ratio, channel orientation angle, rib pitch-to-height ratio (P/e), and number of ribbed walls on friction factor in orthogonally rotating channel with detached ribs. The ribs are separated from the base wall to provide a small region of flow between the base wall and the ribs. Experiments have been conducted at Reynolds number ranging from 10000–17000 with rotation numbers varying from 0–0.38. Pitch-to-rib height ratios (P/e) of 5 and 10 at constant rib height-to-hydraulic diameter ratio (e/D) of 0.1 and a clearance ratio (C/e) of 0.38 are considered. The rib angle of attack with respect to mainstream flow is 90∘. The channel orientation at which the ribbed wall becomes trailing surface (pressure side on which the Coriolis force acts) is considered as the 0∘ orientation angle. For one-wall ribbed case, channel is oriented from 0∘ to 180∘ about its axis in steps of 30∘ to change the orientation angle. For two-wall ribbed case, the orientation angle is changed from 0∘ to 90∘ in steps of 30∘. Friction factors for the detached ribbed channels are compared with the corresponding attached ribbed channel. It is found that in one-wall detached ribbed channel, increase in the friction factor ratio with the orientation angle is lower for rectangular channel compared to that of square channel for both the pitch-to-rib height ratios of 5 and 10 at a given Reynolds number and rotation number. Friction factor ratios of two-wall detached ribbed rectangular channel are comparable with corresponding two-wall detached ribbed square channel both under stationary and rotating conditions.